Peningkatan Hasil Belajar Matematika Penjumlahan Dengan Menggunakan Media Benda Konkrit Sedotan Pada Peserta Didik Kelas 1 MI Muhammadiyah Madureso Kebumen - Rachmayanti, Aulia; Oktaviana, Dwi; Mulyaningrum, Rika; Alfina, Nurdiana; Sahrulita, Fayza (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2025)
This research aims to describe improving learning outcomes through the concrete application learning media in the form of straws in mathematics subjects for class I students. The type of research used is Classroom Action Research (PTK). The research subjects used were 30 students in class I at MI Muhammadiyah Madureso Kebumen for the 2023/2024 academic year as recipients of the action, while those providing the action were researchers and class I’s homeroom teachers. The data collection methods used were observation, tests each cycle and documentation. This classroom action research was carried out in two cycles, each cycle consisting of planning, action, observation and reflection. The results of the research stated that the mathematics learning results of the sum of the material in the first cycle of 30 students were 22 students who completed it and 8 students who did not complete it with a percentage of 26% did not meet the minimum completeness limit, then in cycle II students who completed it were 27 out of 30 students with a percentage 90% have met the minimum completion limit.